Whole-genome sequencing of African swine fever virus from wild boars in the Kaliningrad region reveals unique and distinguishing genomic mutations - Mazloum, Ali; van Schalkwyk, Antoinette; Shotin, Andrey; Zinyakov, Nikolay; Igolkin, Alexey; Chernishev, Roman; Debeljak, Zoran; Korennoy, Fedor; Sprygin, Alexander V. (Frontiers in Veterinary Science, 2023)
Since the first report of outbreaks of African swine fever (ASF) in Georgia in 2007, the disease has expanded into Europe, Russia, and Asia, spreading rapidly via contact with infected animals including domestic pigs and wild boars. The vast expansion of this Genotype II African swine fever virus (ASFV) across wide-ranging territories and hosts inevitably led to the acquisition of novel mutations. These mutations could be used to track the molecular epidemiology of ASFV, provided that they are unique to strains restricted within a certain area. Whilst whole-genome sequencing remains the gold standard for examining evolutionary changes, sequencing of a single locus with significant variation and resolution power could be used as a rapid and cost-effective alternative to characterize multiple isolates from a single or related outbreak. Here, ASFVs obtained during active ASF outbreaks in the Russian region of Kaliningrad between 2017 and 2019 were examined. Since all of the viruses belonged to Genotype II and no clear differentiation based on central variable region (CVR) sequencing was observed, the whole-genome sequences of nine ASFV isolates from this region were determined. To obtain insights into the molecular evolution of these isolates, their sequences were compared to isolates from Europe, Asia, and Africa. Phylogenetic analysis based on the whole-genome sequences clustered the new isolates as a sister lineage to isolates from Poland and Germany. This suggests a possible shared origin followed by the addition of novel mutations restricted to isolates from this region. This status as a sister lineage was mirrored when analyzing polymorphisms in MGF-505-5R and MGF-110-7L, whilst a polymorphism unique to sequences from Kaliningrad was identified at locus K145R. This newly identified mutation was able to distinguish the isolates obtained from Kaliningrad with sequences of Genotype II ASFVs available on GenBank. The findings of this study suggest that ASFVs circulating in Kaliningrad have recently obtained this mutation providing an additional marker to the mutations previously described.